2021
DOI: 10.3389/fpsyg.2021.743504
|View full text |Cite
|
Sign up to set email alerts
|

Body Mobility and Attention Networks in 6- to 7-Year-Old Children

Abstract: Learning in 6- to 7-year-old children is strongly influenced by three functions of attention: alertness, orienting, and executive control. These functions share a close relationship with body mobility, such as the posture adopted or a request to stay still during tasks. The aim of this study (ClinicalTrials.gov) was to analyze the influence of body posture (standing versus sitting) and the influence of these imposed postures compared to a free body mobility on attention functions in 6- to 7-year-old children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…Among TC, we found no significant difference in MedRT between the three body mobility conditions during incongruent trials. Moreover, among TC, we previously showed that the difference between incongruent and congruent trials was more important in the sitting-still posture than in the standing-still posture ( 32 ), suggesting that the sitting-still and standing-still postures have opposite effects between PC and TC. These results are summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Among TC, we found no significant difference in MedRT between the three body mobility conditions during incongruent trials. Moreover, among TC, we previously showed that the difference between incongruent and congruent trials was more important in the sitting-still posture than in the standing-still posture ( 32 ), suggesting that the sitting-still and standing-still postures have opposite effects between PC and TC. These results are summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 97%
“…Regarding the function of attention, alertness ( 38 , 39 ), and to a lesser extent executive control ( 40 43 ), but not orienting ( 38 ), may be improved in a standing compared with a sitting posture. We also previously demonstrated that in TC of 6–7 years of age, standing may improve executive control compared with a sitting posture ( 32 ). Spontaneous body motions and adopting a standing/upright posture may enable children to increase cortical arousal ( 40 , 44 46 ).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations